# Converse of a Conditional Statement

How to find the converse of a conditional statement: examples and their solutions.

## How to Find

The converse of a *p* → *q* is *q* → *p*.

To find the converse,

switch *p* and *q*.

Conditional statement: hypothesis and conclusion

## Example 1

*p*: 2 is a prime number.*q*: 2 is an odd number.

So *q* → *p*:

If 2 is an odd number (*q*),

then 2 is a prime number (*p*).

## Example 2

*p*: He is not in his room.*q*: He is playing basketball.

So *q* → *p*:

If he is playing basketball,

then he is not in his room.